2019
DOI: 10.1515/zpch-2019-1424
|View full text |Cite
|
Sign up to set email alerts
|

From Bulk to Atoms: The Influence of Particle and Cluster Size on the Hydrogen Evolution Reaction

Abstract: To investigate the influence of particle size in terms of electrocatalysis for the hydrogen evolution reaction (HER), small Ptn species with $n=1,10,13$ atoms and nanoparticles are deposited onto native titanium dioxide. These species are compared to the bare support as well as to bulk platinum with respect to the catalytic activity. Photoelectron spectroscopy showed Pt4f core-level shifts to higher binding energies with decreasing cluster size. In addition, the various species contribute significant density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…The results were explained by the overall amount of accessible Pt. No clear trend in the electronic structure emerged with respect to the Pt 4f 7/2 core levels . These theoretical and experimental results explain the behavior depicted in Figure thoroughly.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The results were explained by the overall amount of accessible Pt. No clear trend in the electronic structure emerged with respect to the Pt 4f 7/2 core levels . These theoretical and experimental results explain the behavior depicted in Figure thoroughly.…”
Section: Discussionsupporting
confidence: 66%
“…No clear trend in the electronic structure emerged with respect to the Pt 4f 7/2 core levels. 42 These theoretical and experimental results explain the behavior depicted in Figure 3 thoroughly. The low or almost absent activity of Pt atoms is rationalized as follows: First, there is a low number of Pt sites compared to a cluster at equal coverage.…”
Section: Photoactivity Of Ni-and Pt-loaded Tio 2 (110)supporting
confidence: 63%
See 2 more Smart Citations
“…The metallic core‐lines can be detected in Pt NPs and bulk Pt, but not in deposited Pt NCs, also suggesting the strong quantum effect of cluster size on the electronic structure (Figure 3c). [ 73 ] Tsunoyama et al found that the electronic structure of Pt NCs (Pt‐n, n = ≈1–45) was closely related to their size. With good energy matching of Pt NCs with SrTiO 3 surface, Pt‐30 showed the highest HER activity per unit of Pt.…”
Section: Approaches To Superior Her Performancementioning
confidence: 99%